2013
DOI: 10.3109/10717544.2013.861659
|View full text |Cite
|
Sign up to set email alerts
|

Self-emulsifying drug delivery system and the applications in herbal drugs

Abstract: Herbal drugs have been used for thousands of years in the east and have had a recent resurgence in popularity among consumers in the west. However, most of herbal drug are poorly soluble and have hydrophobic properties and poor distribution, leading to reduced bioavailability and hence decreased treatment efficacy, requiring repeated administration or increased dose. In the past few decades, considerable attention has been focused on the development of self-emulsifying drug delivery system (SEDDS) for herbal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 99 publications
1
40
0
8
Order By: Relevance
“…Self-emulsifying nanoemulsions formulated using Solutol HS and PEG 400 or Transcutol were highly unstable. This may be because of high thermodynamic instability when Solutol HS was mixed with either PEG 400 or Transcutol (Zhang et al, 2015). Self-emulsifying nanoemulsions formulated with a combination of Tween 80 and Transcutol displayed instability, which might be due to a shift in HLB towards hydrophobic side because of low HLB of Transcutol.…”
Section: Discussionmentioning
confidence: 99%
“…Self-emulsifying nanoemulsions formulated using Solutol HS and PEG 400 or Transcutol were highly unstable. This may be because of high thermodynamic instability when Solutol HS was mixed with either PEG 400 or Transcutol (Zhang et al, 2015). Self-emulsifying nanoemulsions formulated with a combination of Tween 80 and Transcutol displayed instability, which might be due to a shift in HLB towards hydrophobic side because of low HLB of Transcutol.…”
Section: Discussionmentioning
confidence: 99%
“…Droplet size is an important factor in SNEDDS formulation because it determines the level and rate of drug release and absorption and increases in bioavailability as well there in vivo stability smaller droplets have a larger surface area, which then increases the level of drug release. The small droplet size may be due to increased surfactant concentration, which forms a closed layer of surfactant at the interface, so as to stabilize dispersed droplets [22]. Therefore, in this study, the nanosize of SNEDDS Singawalang leaves extract might allow it to be more easily delivered into cells or to pass across some barriers.…”
Section: Characterizations Of Snedds Of Extract Singawalang Leavesmentioning
confidence: 88%
“…The first one was to entrap hydrophilic ASD into SNEDDS which was widely employed for poorly water-soluble drugs. [24][25][26] Previous studies demonstrated that phospholipid complexes could improve the liposolubility and oral absorption of the hydrophilic drug. 10,12,27 Thus, APC was prepared, and the liposolubility significantly increased 11.4-fold after formation of APC, which was verified by the solubility test in n-octanol.…”
Section: Discussionmentioning
confidence: 99%
“…26 Grade of different weight ratios of surfactant/cosurfactant is shown in Table 1. The results clearly indicated that Polyoxyl 35 castor oil was more effective in making a grade I nanoemulsion, and it was preliminarily chosen as the surfactant in the system.…”
Section: Selection Of Surfactantmentioning
confidence: 99%
See 1 more Smart Citation